Bio-indicator Bacteria Levels in Riva Stream, an Important Stream in İstanbul, Türkiye - Serap Koşal Şahin; Selma Dilara Karaman Baş; Meryem Öztaş; Gülşen Altuğ; Pelin Saliha Çiftçi Türetken (Aquatic Sciences and Engineering)
Bacterial pollution is the presence of harmful bacteria in aquatic ecosystems, which can cause health problems if ingested. These bacteria originate from a variety of sources, including human and animal waste, agricultural runoff, and untreated sewage. This study aimed to assess the levels of bioindicator bacteria and their associations with various environmental parameters in surface water samples. The samples were collected seasonally from five stations along Riva Stream between March 2018 and January 2019. Indicator bacterial levels were determined using membrane filtration. Temperature, salinity, pH, dissolved oxygen, and conductivity values of the stations were measured in situ during sampling using a multiparameter (YSI). As a result of the sampling, maximum total coliform, fecal coliform, and intestinal enterococci levels were recorded as 24 x 103 CFU/100ml, 18 x 103 CFU/100ml and 24 x 102 CFU/100 ml, respectively. During sampling, the indicator bacterial levels were above the limit at all stations. When the FC/IE ratios were analyzed, the maximum FC/IE ratio was recorded as 52.10 during the winter sampling period at the station. The detection of bioindicator bacteria levels above the standard limit throughout the sampling period (especially during the summer period) was associated with a high level of domestic waste in the region. The results showed that more frequent and detailed monitoring studies should be conducted in this region.